Evaluating the contributions of the community-based resource management project (CBRMP) as a management strategy for upland community development and forest restoration in Brgy. Usmad, Argao, Cebu, Philippines - Malaki, Archiebald Baltazar B. (Cebu City University of the Philippines in the Visayas-Cebu College, 2006)
The Community-based Resource Management Project (CBRMP) in Argao, Cebu was evaluated for its effectiveness in empowering the recipient community and improving the status of the forest resources in the study site. A survey was conducted among the project beneficiaries inBrgy. Usmad from January to March 2006 to determine the impacts of the project on beneficiaries household income, level of awareness on the importance of forest resources, their participation in various project activities, condition of the forest and other naturaresources and the various problems in implementing the projects and their potential solutions as identified by the respondents. Two groups of respondents were involved in the survey : a) project beneficiaries ; and b) project implementors. In site improvement on the survival and growth of reforestation species and fruit trees in tree plantation and agroforestry farm was also conducted. Results of the study show that the respondents were moderately empowered economically, socially and intellectually but highly empowered politically. Respondent's average monthly hosehold income has increased significantly (p<0.00) by 92% from their income without the project. Also the beneficiaries were involved in almost all planning and decision-making processes in project implementation.But some decisions were done solely at the municipal level especially on matters involving budgetary allocation. In addition, theable to reforest about 98.6% of the target areas. Survival rate of reforested areas was pegged at65.9% with an average height of 1.6 m and average diameter of 18.1 mm. Also, about 70% ofthe target areas for agroforestry was established as agroforestry farm. Survival rate of planted trees was estimated to be 73.2% and the average height measured in this farm was 2.76 mwhile the average diameter was 44.6 mm. Among the fruit trees planted jackfruit had the highest survival rate (68.3%) while mango had the lowest (28.3%). The average heightmeasured 1.82 m whereas the average diameter was 18.82 mm of all the fruit trees planted. The level of participation was not significantly correlated with the survival rate of planted treesand fruit trees in tree plantation and in agroforestry farms. The mean survival rate in tree plantation obtained from in situ assessment is significantly difference (p<0.05) with what is obtained from the interview. Whereas, the survival rate of planted mahogany trees and fruit trees like jackfruit and avocado based from in situ has no significant difference with survivalobtained from the interview. However, the survival rate of mango and pomelo based from in situ is significantly different from the survival acquired from the interview with (p<0.01). Thetwo very serious problems identified by the respondents in the area are the scarcity of water and low soil fertility resulting to poor growth of planted seedlings and low farm productivity. Observance of the planting season and proper choice of species to e planted are the two very effective solutions they have identified.
Thesis (M.S. Environmental Studies) -- Cebu City : U.P. in the Visayas-Cebu College, May 2006..